hello, i was wondering if anyone could help me!

i am stuck on a particular question with my maths homework set over the holidays. can you help with this: simplify and express with no denominator

(1/sqrt(x) -sqrt(x))^2

(1 over square root of x - square root of x) all squared

i am also stuck on this one: 2cos^2x - 1 = 1-2sin^2 x

please help, i am rather confused :S

**0**

# homework help

Started by HelpMyDadsAhippy, Jul 26 2010 04:21 PM

1 reply to this topic

### #1

Posted 26 July 2010 - 04:21 PM

### #2

Posted 29 August 2010 - 10:56 PM

(a-b)^2 = a^2 + b^2 - 2ab

so, (1/sqrt(x) -sqrt(x))^2 = 1/x + x - 2*(1/x)*x = x + 1/x - 2

cos^2x = 1 - sin^2 x

so, 2cos^2x - 1 = 2(1-sin^2 x) - 1 = 2 - 2sin^2 x - 1 = 1 - 2sin^2 x

Edinburgh Physics and Maths Tutor

www.physics-maths.co.uk

tutor@physics-maths.co.uk

My link

so, (1/sqrt(x) -sqrt(x))^2 = 1/x + x - 2*(1/x)*x = x + 1/x - 2

cos^2x = 1 - sin^2 x

so, 2cos^2x - 1 = 2(1-sin^2 x) - 1 = 2 - 2sin^2 x - 1 = 1 - 2sin^2 x

Edinburgh Physics and Maths Tutor

www.physics-maths.co.uk

tutor@physics-maths.co.uk

My link

#### 1 user(s) are reading this topic

0 members, 1 guests, 0 anonymous users